Karakteristik Model Quantum Learning Dalam Pendidikan Anak Usia Dini - Ahmad Zain Sarnoto; Ely Budiyanti (UIN Sultan Maulana Hasanuddin Banten, 2021)
This study explores the characteristics of Quantum Learning in early childhood education institutions that are characterized by Islam. The main elements of Qurantum are oriented towards the growth and development of active and participatory learners. The role of early childhood teachers is more as a mentor or facilitator, and not a presenter of universal science, because in the qurantum, knowledge cannot be transferred from teacher to child without the child's own activity. Therefore, teachers need to know in advance how children think, develop and appreciate children's experiences and thinking patterns, by using a variety of learning methods that allow children to actively construct knowledge. Qualitatively descriptive, this research was conducted by taking the research location in RA Bait Qur'any at-Tafkir Tangerang Selatan. It can be concluded that his main character rests on the formation of the Islamic personality. Two patterns are used, namely aqliyah and nafsiyah. The Aqliyah approach is the process of linking facts to tsabiqoh edicts. The Nafsiyah approach is that the teacher acts as a mother, that is, giving sacrificial love, conveying the hopes and souls of the teacher with the students unifying. Keywords: characteristics, Quantum Learning, Teaching Model, early childhood educationReferencesAisyah, S. (2018). Wawancara Kepala Sekolah RA Bait Qur’any. An-Nahlawi, A. (1996). Ushulut Tarbiyah Islamiyah Wa Asalibiha fii Baiti wal Madrasati wal Mujtama (terj). Gema Insani Pres. Arifudin, W. A., Fatihah, N., Echsan, A., Maftuhah, L., Nadjih, D., & Pandoman, A. (2019). Kesadaran Beragama Pelaku Pariwisata di Kawasan Malioboro. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 4(2), 117–132. https://doi.org/10.47200/jnajpm.v4i2.559Aunurrahman. (2011). Belajar dan Pembelajaran. Alfabeta. DePorter, B. (1992). Quantum Learning: Unleashing the Genius in You. Dell Publishing. Fadlullah. (2017). Pendidikan Anak Usia Dini dalam Perspektif Islam. Ta’dib: Jurnal Pendidikan Islam, 6(2), 65–74. https://doi.org/10.29313/tjpi.v6i2.3195Hermawan, T. (2016). Pengaruh Kemampuan Bertanya Terhadap Hasil Belajar. Intersections, 1(1). Hikmah, N. (2018). Wawancara Nurul Hikmah, Ketua Yayasan Bait Qur’any. Idris Usman, M. (2012). Model Mengajar Dalam Pembelajaran: Alam Sekitar, Sekolah Kerja, Individual, Dan Klasikal. Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 15(2), 251–266. https://doi.org/10.24252/lp.2012v15n2a10 Intan. (2018). Wawancara dengan Murid. Jami’un Nafi’in, Muhamad Yasin, & Ilham Tohari. (2017). Konsep Pendidikan Anak Dalam Perpektif Al-Qur ’ an. Edudeena, 1, 9–19. Moedjiono. (2000). Strategi Belajar Mengajar. Kemendikbud Dirjen Pendidikan Tinggi. Nadjih, D., & Imroatun, I. (2016). Hadits Tentang Pendidikan Jasmani Anak Usia Dini. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 51–64. Nanang Hanafiah, C. S. (2010). Konsep Strategi Pembelajaran. Refika Aditama. Nia. (2018). wawancara dengan Wali Murid RA BQ. Nugraha, A. (2014). Pengembangan Pembelajaran. Mitra Mandiri. Rahayu, S. H., Haroen, H., Budiutomo, T., Khasanah, N., & Nuryati, N. (2020). Manajemen Mutu Layanan Ta’lim Quran lil Aulad (TQA) di Yayasan Team Tadarus “AMM” Yogyakarta. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(2), 117–130. https://doi.org/10.47200/jnajpm.v5i2.578Salamah. (2006). Pengembangan Model-model Pembelajaran Alternatif bagi Pendidikan Islam, Suatu Alternatif Solusi Permasalahan Pembelajaran Agama Islam. Fikrah. Sari. (2018). Wawancara dengan Sari, guru kelas RA. Sarnoto, A. Z. (2011). Aktualisasi Pemikiran Pendidikan Akhlak Ibnu Maskawaih Dalam Pendidikan. Jurnal Statement, 1(1), 72–82. Sarnoto, A. Z. (2014). Kecerdasan Emosional Dan Prestasi Belajar: Sebuah Pengantar Studi Psikologi Belajar. In Statement (Vol. 4). Sarnoto, A. Z. (2017). Aspek Kemanusiaan Dalam Pembelajaran Humanistik Pada Anak Usia Dini. Satori, D. (2016). Metode Penelitian. PT Insan Cendekia. Sujiono. (2013). Pendidik Adalah Guru. Citra Press. Umam, M. K., & Syamsiyah, D. (2020). Konsep Pendidikan Humanistik Ki Hadjar Dewantara dan Relevansinya Terhadap Desain Pembelajaran Bahasa Arab. EDULAB: Majalah Ilmiah Laboratorium Pendidikan, 4(2). https://doi.org/10.14421/edulab.2019.42-04Umayah, U., Juhri, J., Muqdamien, B., Fauzia, W., & Maulida Qolbiyah, S. M. (2021). PENGGUNAAN BALOK CUISENIARE UNTUK MEDIA PENGENALAN BILANGAN BAGI ANAK USIA DINI. Intersections, 6(1), 34–42. https://doi.org/10.47200/intersections.v6i1.590Uno, H. B. (2009). Model Pembelajaran Menciptakan Proses Belajar Mengajar yang Kreatif dan Efektif. Bumi Aksara. Yusuf, I. (2018). Wawancara dengan Istikharoh Yusuf.